Association Between Serum Iron Levels and Glycosylated Hemoglobin (HbA1c) in Libyan Male Patients with Type 2 Diabetes: A Pilot Case-Control Study - Eman Almaky; Selma Sarour (AlQalam Journal of Medical and Applied Sciences, 2026)
Glycosylated hemoglobin (HbA1c) is the primary biomarker for long-term glycemic control in diabetes mellitus. However, its validity may be compromised by hematological conditions like iron deficiency anemia (IDA), prevalent in developing regions. This study investigated the association between iron status and HbA1c levels in Libyan patients with Type 2 Diabetes Mellitus (T2DM). A case-control study was conducted at a diabetic center in Al-Bayda, Libya, in August 2023. The study included 52 adult males: 26 T2DM patients and 26 healthy controls matched for age and BMI. Biochemical parameters (HbA1c, serum iron, fasting plasma glucose), anthropometric measurements (BMI, waist circumference), and blood pressure were assessed. Statistical analysis employed t-tests, Pearson correlation, and Chi-square tests using SPSS version 26. The T2DM group had significantly lower mean serum iron (87.2 ± 12.3 µg/dL) than controls (93.5 ± 10.8 µg/dL, p=0.047). A significant negative correlation existed between HbA1c and serum iron (r = -0.331, p = 0.019). Chi-square analysis confirmed a significant association between iron status and glycemic category (χ² = 8.321, p = 0.016). No significant correlations were found between HbA1c and BMI or between iron and BMI. Iron deficiency was significantly associated with elevated HbA1c levels in Libyan T2DM patients, potentially leading to misinterpretation of glycemic control. We recommend incorporating iron status assessment in the routine management of diabetic patients, particularly those with unexplained HbA1c elevations.